Introduction of a junior doctors' handbook: an essential guide for new doctors. Issue 1 (8th February 2016) - Ross, Daniella; Petrie, Claire; Tully, Vicki
Abstract: The transition period for new junior doctors is a daunting and challenging time, as vast amounts of information specific to each hospital, ward, and job must be learnt while maintaining patient care standards.[1] In NHS Tayside, Scotland, tips and guidance for each job are informally handed over from previous junior doctors to the next, resulting in an unreliable and unsustainable handover of information. Time must then be spent by new doctors learning the intricacies and practicalities of their new job, rather than spending time focusing on patient care. Our aim was to improve this transition period for new junior doctors to NHS Tayside through the creation and implementation of a junior doctors' handbook, which would provide information and practical advice on day to day life as a junior doctor. We hoped to implement this project by August 2015 to coincide with the arrival of these new doctors to NHS Tayside. Through repeat PDSA cycles we created a sustainable and reliable junior doctors' handbook, containing a centralised hub of information for doctors that was accessible through our health board's website. The junior doctors' handbook has been a highly beneficial resource that has been praised for its detailed information on all aspects of day to day life for doctors in NHS Tayside. Feedback also demonstrated that doctors felt the junior doctors' handbook had improved their efficiency. Our hope is that this project can continue to be developed within our hospital, but also to be used as an idea outside our health board to improve the transition period for new doctors on a wider scale.